eXcitingTrails/Events: Events for Touristic Scenarios - Belchior, Ana Isabel; Rodrigues da Silva, Alberto (Cadernos de Informática, 2011)
The Internet's availability and the growth of Information and Communication Technologies are increasingly being used in benefit of tourism and culture. This project's main goal is to explore innovative solutions to make tourism more appealing. In the scope of the eXcitingTrails initiative, this proposal consists on the creation and promotion of different events for different environments through a web application that manages a small community of users. To enrich this system, a mobile guide, that takes advantage of positioning and wireless communication, is developed to support the realization of these events. The usage scenarios involve leisure activities, like guided or autonomous walks, or even ludic and competitive games, such as peddypapers where visitors can better discover or learn cultural and historical information about a specific area of interest while playing a game and socializing with other visitors.